2012
DOI: 10.1055/s-0032-1301901
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Erythropoietin on Glucose Metabolism

Abstract: We purposed to determine the impact of erythropoietin on altering glucose metabolism in the settings of in vitro and in vivo experiments. The acute effect of erythropoietin on lowering blood glucose levels was studied in animal experiments. In [³H]-deoxy-D-glucose isotope studies we measured glucose uptake with insulin and erythropoietin using 3T3-L1 cells cultured under normal or high glucose conditions. Altered activation of Akt and ERK pathways was evaluated in immunoblot analyses. Immunocytochemistry was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
2
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 21 publications
(23 reference statements)
1
14
2
4
Order By: Relevance
“…A single injection of a high dose of EPO induced transient phosphorylation of AKT without altering systemic levels of glucose, indicating that EPO-induced phosphorylation of AKT in skeletal muscle has a limited role in acute glucose control in animals with normal blood glucose levels. In contrast, results described in a previous report indicated that acute EPO injection in streptozotocin-induced diabetic rats with elevated blood glucose levels (approximately 22 mM) led to a small (6%) but significant decrease in blood glucose levels; however, the tissues involved have not been identified (Mikolás et al 2012). Initial blood glucose levels may thus be critical in the acute effect of EPO, consistent with the study reporting that hyperglycemia is necessary for stimulation of EPO-induced glucose uptake in adipocytes (Mikolás et al 2012).…”
Section: Discussioncontrasting
confidence: 74%
See 4 more Smart Citations
“…A single injection of a high dose of EPO induced transient phosphorylation of AKT without altering systemic levels of glucose, indicating that EPO-induced phosphorylation of AKT in skeletal muscle has a limited role in acute glucose control in animals with normal blood glucose levels. In contrast, results described in a previous report indicated that acute EPO injection in streptozotocin-induced diabetic rats with elevated blood glucose levels (approximately 22 mM) led to a small (6%) but significant decrease in blood glucose levels; however, the tissues involved have not been identified (Mikolás et al 2012). Initial blood glucose levels may thus be critical in the acute effect of EPO, consistent with the study reporting that hyperglycemia is necessary for stimulation of EPO-induced glucose uptake in adipocytes (Mikolás et al 2012).…”
Section: Discussioncontrasting
confidence: 74%
“…In contrast, results described in a previous report indicated that acute EPO injection in streptozotocin-induced diabetic rats with elevated blood glucose levels (approximately 22 mM) led to a small (6%) but significant decrease in blood glucose levels; however, the tissues involved have not been identified (Mikolás et al 2012). Initial blood glucose levels may thus be critical in the acute effect of EPO, consistent with the study reporting that hyperglycemia is necessary for stimulation of EPO-induced glucose uptake in adipocytes (Mikolás et al 2012). As we have also shown that rat soleus muscle did not express EPOR, AKT activation in our model is likely to be indirect via a still unknown mechanism (Wang et al 2014).…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations